Association of Routinely Measured Proinflammatory Biomarkers With Abnormal MRI Findings in Asphyxiated Neonates Undergoing Therapeutic Hypothermia - Ruhfus, Maria; Giannakis, Stamatios; Markus, Mona; Stein, Anja; Hoehn, Thomas; Felderhoff-Mueser, Ursula; Sabir, Hemmen (Frontiers in Pediatrics, 2021)
Background: The neuroprotective treatment effect of therapeutic hypothermia (TH) following perinatal asphyxia may be negatively influenced by neonatal sepsis and concomitant inflammation. We aimed to correlate routinely used blood biomarkers for perinatal sepsis in cooled asphyxiated newborns with MRI findings. Methods: Perinatal data was retrospectively collected from 67 cooled asphyxiated newborns. Levels of C-reactive protein (CRP), white blood cells and platelets were analyzed before, during and after TH. Interleukin-6 blood levels were analyzed before initiation of TH. Magnetic resonance imaging (MRI) on postnatal day 5-7 was used defining short-term outcome. Adverse outcome was defined as death or adverse MRI findings. Amplitude-integrated electroencephalography (aEEG) was additionally analyzed and correlated with short-term MRI outcome. Results: Forty-nine newborns had favorable short-term MRI outcome. Perinatal data referring to perinatal sepsis did not differ significantly between groups. IL-6 levels before initiation of TH and CRP levels on day three and after TH were significantly higher in newborns with adverse short-term MRI outcome. Males with adverse short-term MRI outcome had significantly increased CRP values at the end of the cooling phase. aEEG strongly correlated with short-term MRI outcome. Conclusion: Routinely used blood biomarkers may be helpful early identifying newborns at high risk of unfavorable outcome and in need of close neurodevelopmental follow-up.